Public obscenity and the formation of emotional legal landscapes in Dries Verhoeven’s Ceci n’est pas... - Päivi Rannila; Siiri Pyykkönen (Taylor & Francis, 2025)
This article addresses the relationships between emotions and the law, and how they define public order and constitute emotional legal landscapes. Using the example of the litigation process of the censorship of Dries Verhoeven’s art installation Ceci n’est pas... we explore the power of individual and collective emotions in acting as a stimulus to the evaluation of the acceptability and legality of artworks in urban public spaces. Verhoeven’s installation was interrupted in Helsinki, Finland, because of public obscenity after a passer-by who was offended by the artwork reported it to the police. This led to a three- year court process, the legal archaeological analysis of which reveals the complex moral geographies in the formation of legal landscapes: the arbitrariness of the interpretation of the law, the significance of time and place in legal evaluation, and the hidden morals included in the understanding of public order. The results show the potential of the concept of emotional legal landscapes in exploring the spatial effects of legal processes, and in revealing how legal reasoning is complex and emotionally laden instead of being carried out by rational legal actors.